Pulmonary embolism: CT findings with the use of helical computed tomography - Grollios, G (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2006)
Aim. The aim of this study is the presentation of the imaging findings in patients with pulmonary embolism, the diagnosis of which was made with the use of helical computed tomography. Material and Methods. The lung CT scans of 14 patients were retrospectively studied. The presence of hypoattenuating thrombus within the lumen of one or more pulmonary arterial branches was considered as the imaging criterion for the diagnosis of pulmonary embolism. Resalts. Emboli within the lumen of 1(st) order branches were found in 2 patients, within the lumen of 2(nd) order branches in 8 patients, into the lumen of 3(rd) order branches (lobar) in 10 patients and into the lumen of 4(th) order branches (segmental) in 6 patients. No emboli were detected in subsegmental or more peripheral branches. Concomitant, secondary findings were the presence of unilateral pleural effusion, areas of pulmonary oligaemia and the presence of a wedge-shaped, pleural-based opacity, indicative of a pulmonary infarct. Conclusion. In conclusion, we were able to make the diagnosis of pulmonary embolism through the direct visualization of intraluminal emboli up until the segmental level, as well as of concomitant, accessory findings of pulmonary embolism.